2023
DOI: 10.3390/cancers15082268
|View full text |Cite
|
Sign up to set email alerts
|

Mannose Inhibits the Pentose Phosphate Pathway in Colorectal Cancer and Enhances Sensitivity to 5-Fluorouracil Therapy

Abstract: Colorectal cancer (CRC) is one of the leading cancers and causes of death in patients. 5-fluorouracil (5-FU) is the therapy of choice for CRC, but it exhibits high toxicity and drug resistance. Tumorigenesis is characterized by a deregulated metabolism, which promotes cancer cell growth and survival. The pentose phosphate pathway (PPP) is required for the synthesis of ribonucleotides and the regulation of reactive oxygen species and is upregulated in CRC. Mannose was recently reported to halt tumor growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Among the 12 qualified drug references, 10 are consistent with the literature descriptions. The literature pertaining to the drug 5-FU, which has the highest frequency, is as follows: in the research by Al Hadeethi et al, it was found that the combined use of 5-fluorouracil (5-FU) and mannose effectively downregulates the pentose phosphate pathway (PPP) to inhibit CRC. This result corresponds to HANSynergy predicting the synergistic effect of 5-FU and mannose in the HCT116 cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 12 qualified drug references, 10 are consistent with the literature descriptions. The literature pertaining to the drug 5-FU, which has the highest frequency, is as follows: in the research by Al Hadeethi et al, it was found that the combined use of 5-fluorouracil (5-FU) and mannose effectively downregulates the pentose phosphate pathway (PPP) to inhibit CRC. This result corresponds to HANSynergy predicting the synergistic effect of 5-FU and mannose in the HCT116 cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, alteration of the PPP contributes directly to cell proliferation, survival and senescence [ 60 ]. Many studies have shown that inhibiting the PPP can inhibit the development of tumors [ 61 , 62 ], but there are currently almost no reports on the regulation of cell death and migration by D-ribouranose 5-phosphate. Interestingly, in this study, the lung cancer cell group treated with Pinellia ternata showed a decrease in D-ribofuranose 5-phosphate expression.…”
Section: Discussionmentioning
confidence: 99%